2021
DOI: 10.1111/acps.13370
|View full text |Cite
|
Sign up to set email alerts
|

Rates of switching stimulants in consecutively referred medication naïve adults with ADHD

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a prevalent, chronic, and morbid, neurobiological disorder estimated to afflict at least 5% of adults in the United States. Due to their well-documented safety and efficacy, the most common treatments for ADHD remain the psychostimulant medicines, methylphenidate (MPH) and amphetamine (AMPH) products. [1][2][3][4] Although both AMPH and MPH products have similar efficacy and tolerability at the group level, 5 little information is available to guide clinicians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Second, patients were followed for a limited time. However, given the frequent non-response in adult ADHD patients in response to any particular stimulant (Adler et al, 2008; Kooij et al, 2004; Spencer et al, 2001, 2005; Ginsberg & Lindefors, 2012; Weiss & Hechtman, 2006) and the high rate of needing to switch adult patients from an initially prescribed stimulant (Biederman, DiSalvo, Green, Woodworth, Gilfix, et al, 2021; Biederman, DiSalvo, Green, Woodworth, Law, et al, 2021), it will be valuable to conduct more comprehensive studies of brain (and perhaps genetic) biomarkers and demographic and clinical measures to optimize the likelihood that ADHD patients can receive effective initial treatment. Third, treatment selection was based on individualized patient needs and profiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, patients were followed for a limited time. However, given the frequent non-response in adult ADHD patients in response to any particular stimulant (Adler et al, 2008; Kooij et al, 2004; Spencer et al, 2001, 2005; Ginsberg & Lindefors, 2012; Weiss & Hechtman, 2006) and the high rate of needing to switch adult patients from an initially prescribed stimulant (Biederman, DiSalvo, Green, Woodworth, Gilfix, et al, 2021; Biederman, DiSalvo, Green, Woodworth, Law, et al, 2021), it will be valuable to conduct more comprehensive studies of brain (and perhaps genetic) biomarkers and demographic and clinical measures to optimize the likelihood that ADHD patients can receive effective initial treatment. Third, treatment selection was based on individualized patient needs and profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Overall response rates are less than 60% among treated adult patients (Adler et al, 2008; Ginsberg & Lindefors, 2012; Kooij et al, 2004; Spencer et al, 2001, 2005; Weiss & Hechtman, 2006). Further, up to 41% of medication-naïve adults diagnosed with ADHD who started stimulant treatment needed to change their initially prescribed stimulant drug to an alternative stimulant family due to low tolerance of the drug’s side effects (Biederman, DiSalvo, Green, Woodworth, Gilfix, et al, 2021; Biederman, DiSalvo, Green, Woodworth, Law, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment duration among all treated patients was longer for LDX and AMP compared with ATX, DEX, MPH, and GXR; patients who switched generally did so more quickly from taking MPH than they did from taking LDX. A recent study found that, among patients prescribed a stimulant first line, 24.0% switched to another agent within 60 days, mostly because of poor tolerability (Biederman et al, 2021). In a Danish study, among 55 children/adolescents with ADHD prescribed MPH first line, 36.0% switched treatments during the first 6 months (Warrer et al, 2016).…”
Section: Discussionmentioning
confidence: 99%